Post‐transplant malignancy in solid organ transplant recipients in Ireland, The Irish Transplant Cancer Group. Issue 10 (30th September 2019) - O'Neill, James Paul; Sexton, Donal J.; O'Leary, Eamonn; O'Kelly, Patrick; Murray, Susan; Deady, Sandra; Daly, Fergus; Williams, Yvonne; Dean, Ben; Fitzgerald, Conall; Murad, Aizuri; Mansoor, Nazish; et al.
Abstract: Objective: Solid organ transplant recipients are at increased risk of cancer compared to the general population. To date, this risk in Ireland has not been investigated. We conducted a national registry study of cancer incidence following solid organ transplantation. Methods: National centers for solid organ transplantation supplied their respective registry databases to cross‐reference with episodes of malignancy from the National Cancer Registry Ireland (NCRI) between 1994 and 2014. Standardized incidence of cancer post‐transplant was compared to the general population by means of standardized incidence ratios (SIRs), and between solid organ transplant types by incidence rate ratios. Results: A total of 3346 solid organ transplant recipients were included in this study. Kidney transplant recipients constituted the majority of participants (71.2%), followed by liver (16.8%), heart (6.4%), and lung (5.6%) transplants. The most common cancers within the composite of all transplant recipients included the following (SIR [95% CI]): squamous and basal cell carcinoma (20.05 [17.97, 22.31] and 7.16 [6.43, 7.96], respectively), non‐Hodgkin lymphoma (6.23 [4.26, 8.59]), and renal cell carcinoma (3.36 [1.96, 5.38]). Conclusions: This study reports the incidence of cancer following solid organ transplantation in Ireland. These results have significant national policy implications for surveillance, and early diagnosis in this patient group.